Evaluating Surface Water Quality of Euphrates River in Al-Najaf Al-Ashraf, Iraq with Water Quality Index (WQI) - Al Sharifi, Suhair Razzaq; Zwain, Hanadi H.; Hasan, Zinah K. (Engineering, Technology & Applied Science Research, 2024)
The present study illustrates the rapid pollution of Euphrates River, inwards Al-Najaf Al-Ashraf governance (Al-Kufa River) in Iraq, which is one of the most important rivers in the region. The river faces formidable pressure due to encroachments, discharge of untreated domestic and industrial waste, drainage water from cultivated orchards, and dumping of solid waste. This study was conducted to assess the temporary and locative organic pollution in the region. Water Quality Index (WQI) of the Al-Kufa river was determined according to the Canadian Council of Ministers of Environment (CCME) method by calculating seven parameters (water temperature, DO, COD, EC, TDS, turbidity, and pH) in two sampling stations. Surface water samples were collected in a period of four months (September to December) in 2023. WQI level, correlation analysis between parameters, and Iraqi and CCME drinking water specification standards were employed to classify the surface water status. The results show that the ecological condition can be classified as marginal with WQI= 49 and poor with WQI= 42 in stations 1 and 2, respectively.